Prognostic value of HLA-I homozygosity in patients with non-small cell lung cancer treated with single agent immunotherapy - Mark Watson; Michael Millward; Samantha Bowyer; Afaf Abed; Leslie Calapre; Johnny Lo; Suzana Correia; Abha Chopra; Muhammad Adnan Khattak; Elin Solomonovna Gray (Journal for ImmunoTherapy of Cancer)
Background We aimed to assess the impact of genomic human leukocyte antigen (HLA)-I/II homozygosity on the survival benefit of patients with unresectable locally advanced, metastatic non-small lung cancer treated by single-agent programmed cell death protein-1/programmed death ligand 1 (PD1/PDL1) inhibitors.Methods We collected blood from 170 patients with advanced lung cancer treated with immunotherapy at two major oncology centers in Western Australia. Genomic DNA was extracted from white blood cells and used for HLA-I/II high-resolution typing. HLA-I/II homozygosity was tested for association with survival outcomes. Univariable and multivariable Cox regression models were constructed to determine whether HLA homozygosity was an independent prognostic factor affecting Overall Survival (OS) and Progression Free Survival (PFS). We also investigated the association between individual HLA-A and -B supertypes with OS.Results Homozygosity at HLA-I loci, but not HLA-II, was significantly associated with shorter OS (HR=2.17, 95% CI 1.13 to 4.17, p=0.02) in both univariable and multivariable analysis. The effect of HLA-I homozygosity in OS was particularly relevant for patients with tumors expressing PDL1 ≥50% (HR=3.93, 95% CI 1.30 to 11.85, p<0.001). The adverse effect of HLA-I homozygosity on PFS was only apparent after controlling for interactions between PDL1 status and HLA-I genotype (HR=2.21, 95% CI 1.04 to 4.70, p=0.038). The presence of HLA-A02 supertype was the only HLA-I supertype to be associated with improved OS (HR=0.56, 95% CI 0.34 to 0.93, p=0.023).Conclusion Our results suggest that homozygosity at ≥1 HLA-I loci is associated with short OS and PFS in patients with advanced non-small cell lung cancer with PDL1 ≥50% treated with single-agent immunotherapy. Carriers of HLA-A02 supertype reported better survival outcomes in this cohort of patients.